Sub‐synchronous oscillation mechanism and its suppression in MMC‐based HVDC connected wind farms. Issue 4 (17th January 2018) - Lyu, Jing; Cai, Xu; Amin, Mohammad; Molinas, Marta
Abstract : A subsynchronous oscillation (SSO) phenomenon in a wind farm integrated with a modular multilevel converter (MMC)‐based high‐voltage direct current (HVDC) transmission system has been recently observed in the real world. An attempt is made in this paper to contribute to the understanding of the root cause of the SSO in the MMC‐HVDC connected wind farms. For that, the small‐signal impedance model of the MMC is first developed based on the harmonic state‐space (HSS) modelling method. An inherent low‐frequency resonance peak in the MMC excluding any control influence is identified by its terminal impedance. Arguably, this could be the reason why the SSO occurs in the MMC‐HVDC connected wind farms. In addition to that, the influence factors, such as main circuit parameters, controller parameters, and power level, on the stability of the interconnected system are examined, which can provide guidelines for the system design in order to guarantee the stability of the interconnected system. Based on the mechanism analysis, a stabilization control for suppressing the SSO in the MMC‐HVDC based wind farms is also proposed. Finally, the theoretical analysis and stabilization control are validated by both time‐domain simulations and field measurements in a real MMC‐HVDC connected wind farm in China.